Mental imagery in the context of online compulsive buying-shopping disorder: The role of pleasure and relief - Annika Brandtner; Matthias Brand; Astrid Müller (Addictive Behaviors Reports)
Background: The rise of e-commerce has led to an increase in online compulsive buying-shopping disorder (OCBSD), an addictive disorder potentially driven by preoccupations like mental imagery, yet their occurrence and predictors have not been thoroughly explored. Methods: This study investigated the expression of and associations with mental imagery in women with pathological (n = 56) or non-problematic buying-shopping (n = 56) applying hierarchical regression analyses. Participants were classified based on a structured diagnostic interview, completed self-report questionnaires assessing experiences of gratification and compensation during shopping, and a 14-day end-of-day ambulatory assessment, evaluating mental imagery intensity. Results: Women with pathological buying-shopping reported significantly more intense shopping-specific mental imagery compared to women with non-problematic buying-shopping. Mental imagery was significantly predicted only by compensatory experiences in the pathological buying-shopping group with medium effect sizes. Discussion: The findings suggest that in OCBSD, mental images likely arise from to the anticipated effects of relief, possibly indicating a maladaptive coping strategy.